AKUNTABILITAS VERTIKAL-HORIZONTAL APARATUR PUBLIK DALAM PERSPEKTIF INTERPRETIVE PHENOMENOLOGY HEIDEGGER - Ardy Fariyansyah; Gugus Irianto; Roekhudin Roekhudin (Jurnal Akuntansi Aktual, 2018)
This research aims to produce a deep understanding of accountability in the public service sector The Local Government District of Malang. This research uses a qualitative research approach with the phenomenology of Martin Heidegger (interpretive phenomenology) that seeks to generate the meaning of accountability from the broader perspective of public employee (dasein) within the scope of the practical work. The results showed that the meaning of accountability included a vertical-horizontal relationship. The improvement of  the quality of public services (in the Local Government District of Malang) requires a mindset change of public employee. A deep understanding of accountability meaning from practical side become a key to improve the quality op public services in the local government.